Exploring nursing students’ awareness, utilization, and satisfaction with barangay health services in the Philippines: Implications for public health and technological advancements in healthcare delivery - Chan, Natasha Kay V.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
This study explores nursing students’ awareness, utilization, and satisfaction with Barangay Health Services in the Philippines during the COVID-19 pandemic. A barangay, the smallest administrative unit in the country, functions as a neighborhood or village providing essential public health services. The objective was to assess how demographic factors influenced students’ interaction with health services such as childhood immunizations, prenatal and postnatal care, and affordable medicine programs. A cross-sectional design was employed, using a structured survey to gather data from 240 nursing students across different year levels. Statistical analysis using Chi-square tests revealed that while nearly 90% of students were aware of these services, less than 20% regularly used them, indicating a significant gap between awareness and actual utilization. The study found that gender and marital status were significant factors influencing the utilization of maternal healthcare services, and year level was associated with increased infant vaccination. The findings underscore the need for improved strategies to enhance access to and utilization of Barangay Health Services. This research suggests that technological advancements and interdisciplinary collaboration among healthcare providers and educators could bridge the gap between awareness and utilization, ensuring more effective healthcare delivery and improved public health outcomes, especially in resource-constrained settings.